Implementasi Pendekatan Saintifik Untuk Meningkatkan Hard Skills Dan Soft Skill Siswa Pada Mata Pelajaran PAI Sekolah - Isroani, Farida; Nisa', Ida Fauziatun (Universitas KH. A. Wahab Hasbullah, 2022)
In the current era of globalization, science and technology are developing rapidly. This has an impact on the learning process in educational institutions. There are three major forces that influence a person's development including civil society, nation-states, and globalization. The scientific approach is intended to provide understanding to students in recognizing, understanding various materials using a scientific approach, that information can come from anywhere, anytime, not depending on direct information from the teacher. This study aims to describe how the implementation of the scientific approach in an effort to improve students' hard skills and soft skills, especially in the subject of Islamic Religious Education. The research method uses descriptive qualitative, including interviews, documentation and observation. The location of the research was carried out at the State High School. The results of this study are that the implementation of the scientific approach is expected to be able to improve students' hard skills and soft skills in Islamic Religious Education subjects.